Considerations of Religious Court Judges in Determining Iddah and Mut'ah Post-Divorce Support - Haeratun (International Journal of Law Analytics, 2024)
The main problem of this research is the view of Islamic law regarding the payment of iddah and mut'ah maintenance for wives who are divorced by their husbands and how religious court judges consider in determining the iddah and mut'ah maintenance of wives after divorce. This research is a type of empirical or non-doctrinal legal research. The results of this research show that Islamic law relating to iddah and mut'ah livelihoods has its legal basis in article 149 letters and b and article 151 KHI. Giving mut'ah is the implementation of Allah SWT's command. To husbands to always associate their wives with the principle of imsakum bil ma'ruf aw tasrihum bi ihhsan (maintaining the marriage bond with kindness or letting go with kindness). The judge determines the amount of iddah and mut'ah support by considering justice and propriety and adapting it to the economic capacity of the ex-husband and the basic needs of the ex-wife and children.